DETECTION EARNINGS MANAGEMENT by DEFERRED TAX EXPENSE and FIRM CHARACTERISTIC - Kisno Kisno; Istianingsih Istianingsih (Jurnal Riset Akuntansi Terpadu, 2016)
Abstract This study aimed to examine the effect of deferred tax expense and the Firm characteristics in a proxy with ROA and leverage to earnings management.The data is analyzed secondary data research company manufacturing year period 2011- 2013. From a population of 426 got 45 samples obtained by using purpose sampling. The analytical method used is multiple linear regression.Statistical test results showed that partially: 1). Deferred tax expense have possitive anda significant  effect on Earning management. 2). Characteristics of the company in a proxy by ROA no impact on earnings management. 3). Characteristics of the company in a Proxy by  leverage have positive and significant impact on earnings management. Keywords: Earnings Management, deferred tax expenses, ROA, Leverage Abstrak Penelitian ini bertujuan untuk menguji pengaruh beban pajak tangguhan dan karakteristik perusahaan dalam proksi dengan ROA dan leverage untuk manajemen laba. Data dianalisis sekunder data penelitian perusahaan manufaktur periode tahun 2011-2013. Dari populasi 426 mendapat 45 sampel yang diperoleh. dengan menggunakan purpose sampling. Metode analisis yang digunakan adalah regresi linier berganda. Hasil uji statistik menunjukkan bahwa secara parsial: 1). Beban pajak tangguhan berpengaruh positif dan signifikan terhadap manajemen Laba. 2). Karakteristik perusahaan dalam proksi oleh ROA tidak berdampak pada manajemen laba. 3). Karakteristik perusahaan dalam Proxy oleh leverage memiliki pengaruh positif dan signifikan terhadap manajemen laba. Kata kunci: Manajemen Laba, beban pajak tangguhan, ROA, Leverage